Pandemi dan Percepatan Pengentasan Digital Divide Pada Kelompok UMKM - Himawan Ardhi Ristanto; Shinta Prastyanti; Adhi Iman Sulaiman (Pena Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
The "digital divide" is a matter of differences in access to information technology opportunities that create disparities between individuals, businesses, and geographic areas at different socioeconomic levels. The increase in internet users in Indonesia reflects the fact that Indonesian society is starting to transform into an information society. The digital divide is classified into two types: First, there is the traditional digital divide, which consists of gaps in internet access and digital technology and the ability to use them optimally. Two: the new digital divide, namely the gap in knowledge about algorithms, data, and information. The COVID-19 pandemic has forced people, especially MSMEs, to adapt to digital technology. This study aims to let the authors know how the pandemic situation has accelerated the alleviation of the digital divide in the MSME group. This study uses a qualitative descriptive method with a literature study. The results of the study show that the pandemic has caused MSMEs to adapt from conventional marketing models to digital marketing. Many MSMEs have been affected by the pandemic, but those that have been able to survive because they have transformed using digital technology. 16.4 million MSMEs are connected to the digital ecosystem, a significant increase during the pandemic. The government was quite responsive during the pandemic, trying to narrow the gap between the traditional digital divide and the new digital divide. The form is encouraging digital inclusion for MSMEs to enter the digital ecosystem in the form of holding online digital training, etc. The government must immediately realize the palapa ring to ensure connections and reduce blankspot areas.